Socio-economic, Demographic and Environmental Relationship of Maijchar Region Bangladesh for Application in Participatory GIS - Baby, Sultana Nasrin; Abbas, Nahlah; Kirkman, Hugh (International Journal of Bio-resource and Stress Management, 2018)
Comprehensive and accurate maps appropriate for decision making at the local level are outmoded or presently not available in the Maichar Union local community, Bangladesh. This paper aims at understanding the use and the consequences of Participatory Geographic Information System (PGIS) in this local community and presents a community map based on Participatory Rural Appraisal (PRA) and Geographic Information System (GIS) practices (particularly photo mapping). It links to advanced spatial analysis in socio-economic, demographic, and environmental-correlation. PRAGIS was applied and examined to identify its likelihood to help local communities of the Maichar Union in the management of their socio-economic, demographic, and environmental condition. Involvement of the local community in identifying their information needs. Gathering data and natural resources information was greatly valuable in combination with GIS. During the assessment of PRAGIS, it was recognized that for developing plans the emphasis should be basically on the primary stakeholder, such as the local community and the poor rather than on technical experts. This rarely takes place at the ground level and could be a restrictive factor for the efficiency of GIS as a participatory tool although it facilitates participating diverse stakeholders to make an appropriate decision by engaging all relevant stakeholders to participate. This study shows that in a developmental context PRAGIS should be viewed primarily as a consultative, participatory methodology rather than a predominantly technological aid. The outcomes of this research have made a major contribution in developing the Maichar Union local community particularly for sanitation and education sectors.